The Study of Six Sigma Practices in Construction Project Management Performance - Johari, Nur Fatimah; Zainal, Rozlin; Kasim, Narimah; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2024)
The construction industry is known for its high risk and complexity, making Six Sigma an ideal methodology for improving project performance management and efficiency. Malaysian construction projects were hampered by the lack of knowledge and understanding about Six Sigma among construction practitioners limited its implementation in Malaysia construction projects. Therefore, the objectives are to identify the main Six Sigma practice in improving project performance towards the construction industry, to study main the effectiveness level of Six Sigma practice in improving project performance construction industry and to examine the relationship between practice with effectiveness level of Six Sigma practice in improving project performance towards construction industry. The study used a quantitative approach to accomplish all its objectives, with the G7 construction companies in Gombak district serving as the respondent. The purpose of this research is to examine the viewpoints of 113 Gombak district Grade 7 contractors’ companies. The survey was distributed to participants via email, WhatsApp, and in-person meetings using a Google Form link. Out of the total number of respondents, 93 (or 82.3%) have provided feedback through the survey. All objectives’ data was evaluated using descriptive statistics, frequency, and crosstabs in SPSS software. The findings of this study, the main practices and main corresponding effectiveness level is Six Sigma practices improve project outcomes and reduce defects and importance of Six Sigma in ensuring its efficiency accordingly was determined as the greatest frequency. Furthermore, the strongest relationship with main practice with its main efficiency level is Knowledge of Six Sigma practices – Ongoing development with Importance of Six Sigma in ensuring its efficiency – Reduce construction carbon impact. This study could help G7 contractor’s companies through research information and framework development as a guideline to adopt Six Sigma practices to improve project performance towards construction industry.